Women’s experiences and expectations of intimate partner abuse identification in healthcare settings: a qualitative evidence synthesis - Kelsey Hegarty; Laura Tarzia; Evangelica Korab-Chandler; Minerva Kyei-Onanjiri; Jacqueline Cameron (BMJ Open)
Objectives To explore women’s experiences and expectations of intimate partner abuse (IPA) disclosure and identification in healthcare settings, focusing on the process of disclosure/identification rather than the healthcare responses that come afterwards.Design Systematic review and meta-synthesis of qualitative studiesData sources Relevant studies were sourced by using keywords to search the databases MEDLINE, EMBASE, CINAHL, PsychINFO, SocINDEX and ASSIA in September 2021.Eligibility criteria Studies needed to focus on women’s views about IPA disclosure and identification in healthcare settings, use qualitative methods and have been published in the last 5 years.Data extraction and synthesis Relevant data were extracted into a customised template. The Critical Appraisal Skills Programme checklist for qualitative research was used to assess the methodological quality of included studies. A thematic synthesis approach was applied to the data, and confidence in the findings was appraised using The Confidence in the Evidence from Reviews of Qualitative research methods.Results Thirty-four studies were included from a range of healthcare settings and countries. Three key themes were generated through analysing their data: (1) Provide universal education, (2) Create a safe and supportive environment for disclosure and (3) It is about how you ask. Included papers were rated overall as being of moderate quality, and moderate-high confidence was placed in the review findings.Conclusions Women in the included studies articulated a desire to routinely receive information about IPA, lending support to a universal education approach that equips all women with an understanding of IPA and options for assistance, regardless of disclosure. Women’s suggestions for how to promote an environment conducive to disclosure and how to enquire about IPA have clear implications for clinical practice.PROSPERO registration numberCRD42018091523.